Influence of 3d transition metals on the stability and elecronic structure of MgH2 - Zeng, X.; Cheng, L.; Zou, J.; Ding, W.; Tian, Hu-yong; Buckley, Craig (American Institute of Physics, 2012)
The effect of minor addition of 3d transition metals on the formation enthalpy (ΔH) and electronic structure of MgH2 have been studied using first-principle calculations, and considering the phonon-calculated zero point energy. The results indicate that the partial substitution of Mg atoms by 3d transition metal atoms increases the formation enthalpy of MgH2. Both formation enthalpy and Mulliken population analysis showed that the ability to destabilize MgH2 generally increases with the atomic number, except Mn and Zn, which have half-filled and completely filled 3d orbital states. The destabilization of MgH2 by partially alloying 3d elements was due to relatively stronger covalent bonds between 3d elements and the H atom, and a weaker ionic bond between Mg and H in the alloyed material with respect to pure MgH2. Based on electronic structure analyses, MgH2 and MgH2 alloyed with Ti, Fe, and Zn show no spin magnetism, while MgH2 alloyed with Sc, V, Cr, Mn, Co, Ni, and Cu show spin magnetism. In the MgH2-3d metal system except Zn, the bonding peak near the Fermi energy is mainly contributed by 3d electrons of transition metals and weak H (s) states. The bonding nature of MgH2 is ionic, and the bonding nature of MgH2-3d metal systems is mainly ionic with covalent bonds between 3d metal atoms and their neighbour H atoms.